Neuropathic pain in athletes: basics of diagnosis and monitoring of a hidden threat - AlMakadma, Yasin; Eirale, Cristiano; Chamari, Karim (Biology of Sport, 2022)
The aim was to increase awareness about neuropathic pain in athletes and the available diagnostic criteria and explore the relevance to athletes and sports. In the report of its consensus meeting of 2016, the International Olympic Committee (IOC) noted the critical need to raise the awareness about pain and its management amongst sports physicians. The adequate management of pain requires recognition of its type and pathophysiological mechanisms. This is paramount in applying the multi-modal management of pain as a symptom or approach it as a disease. In athletes, the assessment of pain in general, and of neuropathic pain in particular, is more complex due to the impact of physiological, psychological and motivational factors and specific pathophysiological mechanisms on the pain threshold and tolerance. Neuropathic pain is not uncommon to encounter in athletes although not always recognised. Examples of neuropathic pain as a disease include complex regional pain syndrome (CRPS), peripheral neuropathy and spinal cord injuries. The recognition and diagnosis of neuropathic pain could be facilitated by the application of screening tools such as DN4 (Douleur Neuropathique 4) and LANSS (Leeds Assessment of Neuropathic Symptoms and Signs). Sports injuries may lead to neuropathic pain through different pathologies and mechanisms. Thus, neuropathic pain could be a real threat to athletes’ career if not promptly recognised and treated. We therefore believe that early recognition and expert management are mandatory for the best outcome.